A Phase I, Randomized, Single-Dose Study Evaluating the Biosimilarity of TAB008 to Bevacizumab in Healthy Volunteers - Wang, Jin; Qi, Lu; Liu, Long; Wang, Zejuan; Chen, Gang; Wang, Yu; Liu, Xiaona; Liu, Ying; Liu, Huijuan; Tong, Yuanxu; Liu, Chen; Lei, Chunpu; et al. (Frontiers in Pharmacology, 2019)
Objective: This study compared the pharmacokinetics (PK), safety and immunogenicity of the biosimilar TAB008 monoclonal antibody to bevacizumab (Avastin®) in normal healthy Chinese male volunteers. Methods: In this randomized, double-blind, parallel controlled study, a total of 100 healthy Chinese male subjects were randomized (1:1) to receive a single 1 mg/kg intravenous dose of TAB008 or Avastin® over a 90-minute infusion. The subjects were followed for 99 days after drug administration. Primary endpoints were bioequivalence of major pharmacokinetic parameters (AUC0-t and AUC0-) and maximum observed serum concentration (Cmax). Secondary endpoints included safety and immunogenicity parameters. Results: The two groups of test subjects (49 subjects in the TAB008 group and 50 subjects in the Avastin® group) were well matched in regards to all demographic and baseline characteristics. The treatment group ratios of LS geometric means for the three primary PK parameters were fully contained within the bioequivalence limits of 80.00–125.00% (90% CI was 103.66–118.33% for Cmax, 94.32–111.72% for AUC0-t, and 94.69–112.23% for AUC0-). Treatment-emergent adverse events (TEAEs) were reported for 24 (49.0%) subjects in the TAB008 group and 22 (44.0%) subjects in the Avastin® group. TEAEs related to the study drug were reported for 19 (38.8%) subjects in the TAB008 group and 19 (38.0%) subjects in the Avastin® group. National Cancer Institute-Common Terminology Criteria for Adverse Events (NCI-CTCAE) Grade 3 TEAEs were reported for 1 (2.0%) subject in the TAB008 group and 3 (6.0%) subjects in the Avastin® group. There were no Grade 4 or 5 TEAEs or Serious adverse events (SAEs) during the study. Anti-drug antibody generation was reported once only in each group, neutralizing antibody (Nab) analysis was negative upon follow-up. Conclusion: TAB008 attained pharmacokinetic similarity to bevacizumab, and was safe and well tolerated.